NUMERICAL SIMULATION AND OPTIMIZATION OF MULTI-CORNER CRASH BOX UNDER AXIAL LOADING - Galang Hastungkorojati, Dhimaz
In modern civilization, as it is today, transportation takes a significant role in human life. As modes of transportation become more diverse and more parties to use and developing them, people increasingly pay attention to the safety of transportation modes. Various kinds of efforts have been given by engineers and policyholders to achieve these goals, some of which regulate the use of seat belts, speed limits, driving attitudes, and road safety. Some of the rules and standards also control the specifications of the vehicle structure for some cases of accidents/collisions that aim to protect the driver/passenger that commonly referred to crashworthiness. The energy absorbing system is one way to increase the safety according to the crashworthiness principal, one of the energy absorbing system that commonly use is the crash box that have a various ways to develop its utilization, such as increasing the thickness, perimeter, and a number of the crash box corner. This final project presents the numerical simulation and optimization process of the multi-corner crash box that have an objective to find the characteristic of the crash box crashworthiness parameter and find the optimum design to maximize the parameter of the crash box under axial loading. The numerical simulation will be done using the explicit finite element method. While the crash-box is fully modelled by the Kriging method to get the most optimum design. The results indicate that MC20 has the best structure efficiency in terms of mean crushing force (Pm) and specific energy absorption (SEA) if it is compared to SQ, CR, MC12, and MC12+. Increasing the thickness is more efficient rather than increasing the perimeter of the crash box to get a better mean crushing force (Pm). Whereas, crushing force efficiency (CFE) can be obtained the highest, in higher thickness but least in the perimeter. Moreover, the highest value of specific energy absorption (SEA) can be obtained at both least of thickness and perimeter.